PENATALAKSANAAN FISIOTERAPI PADA KASUS ISCALGIA DENGAN MODALITAS TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION DAN TERAPI LATIHAN - Alexander Alexander; Maryaningsih Maryaningsih (Jurnal Kesehatan dan Fisioterapi, 2023)
Background: : Ischialgia is a condition that causes the patient to experience pain and/or paresthesias in the distribution of the sciatic nerve or the associated lumbosacral nerve root. The physiotherapy intervention given to ischialgia cases is by administering Transcutaneous Electrical Nerve Stimulation (TENS) therapy modalities and Mc.Kenzie Exercise therapy. The purpose of this study was to determine the benefits of TENS administration in reducing pain in ischialgia and the effect of Mc.Kenzie Exercise therapy on increasing joint range of motion and functional ability in ischialgia sufferers. This research method is a case study with a pretest-posttest design. The research subject was a 45 year old woman who was diagnosed with ischialgia. Subjects were given TENS intervention for 20 minutes and Mc.Kenzie Exercise therapy for 30 minutes, three times a week for four weeks. The results showed that after four weeks of therapy, the assessment results for silent pain from T1: 6 to T3: 2 (based on a numerical pain scale), tenderness from T1: 5 to T3: 3 (based on an algometric pain scale), pain motion from T1:5 to T3:3 (based on a numerical pain scale). Increase in joint range of motion during flexion from T1: 3 cm to T3: 6 cm, extension from T1: 2 cm to T3: 6 cm (based on goniometric measurements). Functional improvement from T1: 40% to T3: 20% (based on the Oswestry Disability Index). The conclusion of this study is the use of TENS modality and Mc.Kenzie Exercise therapy can help reduce pain in the lower back and increase functional activity and range of motion in the lower back in patients with ischialgia...Keywords: Ischialgia, Tens, Exercise therapy